Analisis Komparatif Pilkada Langsung dan Tidak Langsung dalam Pemilihan Kepala Daerah di Indonesia Perspektif Siyāsah Dustūriyyah - Salwa Alya Zahra; Irwansyah (Aksioreligia, 2026)
This study aims to analyze the implementation of direct and indirect regional head elections based on Indonesian legislation and to examine both mechanisms from the perspective of siyāsah dustūriyyah. This research employed a normative legal research method using statutory, comparative, and conceptual approaches. The legal materials consisted of primary, secondary, and tertiary sources, which were analyzed qualitatively through library research. The findings indicate that the mechanism for regional head elections under Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia constitutes an open legal policy, allowing either direct elections or indirect elections through the Regional People's Representative Council (DPRD). However, under Law Number 10 of 2016, the prevailing mechanism remains direct regional head elections, providing direct political legitimacy from the people. From the perspective of Siyāsah Dustūriyyah, both mechanisms are acceptable as long as they uphold the principles of shūrā (consultation), al-'adl (justice), al-amānah (trustworthiness), and maṣlaḥah (public interest). Nevertheless, direct regional head elections are considered more relevant to the principle of popular sovereignty in the current Indonesian constitutional system, while indirect elections may only reflect the concept of ahl al-ḥall wa al-'aqd if conducted by representative institutions possessing integrity and prioritizing public welfare.